(untitled) (Revista Rupturas, 2025)
In this article we analyze the extent to which the Limonense Creole language has been kept alive by the Afro-Limonense population both in the province of Limon and in the Greater Metropolitan Area (GAM) where many have migrated in the last 20 years in search of better educational and employment opportunities. Limonese Creole is a minority language, which is orally transmitted and maintained. In Limon, it is used naturally in intimate contexts such as the family, in religious and cultural activities, and among groups of friends, as the main form of socialization, along with Spanish. It is used mainly by adults and older adults, but not among the young and child population because it has not been valued within the Afro-Limonense community itself. This study reports the perceptions that the Afro Limenese population in Limon has about this language and compares these perceptions with those provided by Afro Limonese people who have migrated to a new sociocultural context where the dominant language is Spanish. In both cases, these people show great esteem for Limonese Creole, despite its weakening in recent years and despite the fact that Spanish is the dominant language for the vast majority; they show interest in maintaining and transmitting it to younger generations, as they consider it an essential part of their identity and a way to maintain a link with their Afro heritage.